PP153 The Economic And Fiscal Impact Of Public Health Programs For Diabetic Patients In Italy. (23rd December 2022) - Di Brino, Eugenio; Basile, Michele; Rumi, Filippo; Calabrò, Giovanna Elisa; Cicchetti, Americo
Abstract : Introduction: Technological innovations in the health sector have economic implications that go beyond their effects on health expenditure, expanding into other areas of the state budget (e.g., the social security system). Furthermore, innovation can affect the production of wealth by workers and companies, which in turn affects tax revenues. In addition, the presence of chronic diseases tends to reduce the propensity to consume and changes the allocation of consumption between the different sectors. Allocative decisions in the health system are rarely supported by an analysis that combines the health effects of innovations and their consequences in the economic system. Methods: The objective of this study was to estimate the value of management programs for patients suffering from type 2 diabetes mellitus that involved different levels of use of innovative technologies and drugs. A tax impact assessment methodology was adopted in the context of chronic conditions to analyze the effect of adopting alternative management models for patients with diabetes on the broader economic system. Results: Assuming a policy that reduces annual complications by 0.42 percent, there was an increase in tax revenue (cumulative value) of approximately EUR 28, 175 and a reduction in productivity losses (cumulative value) of EUR 4, 049, 890. Projecting the impact on the age trend of the population up to 65 years of age with these estimates, it is possible to have an increase in tax revenue (cumulative value) equal to approximately EUR 7, 050, 598 and a reduction in productivity losses (cumulative value) equal to EUR 140, 235, 923. Conclusions: In light of this work, providing remote patient support (telemedicine) and expanding the provision of innovative oral antidiabetic drugs to family physicians could improve care for patients with type 2 diabetes mellitus. This study provides decision makers with an immediately usable model to broaden the information base for planning and regulatory choices. In addition, it supports the use of economic evaluations that calculate the entire value of a technological innovation or health program.